Cross purposes: the violent grammar of Christian atonement - Bartlett, Anthony W. (Bloomsbury Publishing PLC, 2001)
Cover -- Half-title -- Title -- Copyright -- Dedication -- Contents -- Introduction -- 1. The Abyss That Is Not Yet Love -- 2. Imitatio Diaboli -- 3. The Warrior Christ and His Pity -- 4. Repetition, Rhetoric, and Compassion -- 5. Cross Talk: Hermeneutics of the Death of Jesus of Nazareth -- 6. Jesus, Time and Again -- Conclusion -- Index